NALAR ISLAM TENAGA EDUKATIF UNIVERSITAS RAHMATAN LIL ALAMIN - Asmuni Asmuni; Muntoha Muntoha; Muhammad Husnul (Millah: Journal of Religious Studies, 2014)
Islamic University of Indonesia (UII) was established by the founding fathers who originated from the background of several Islamic organizations in Indonesia. such as Nahdlatul Ulama (NU) and Muhammadiyah, etc. so that the vision of UII, is rahmatan lil ‘alamin. Starting from this vision, then this research traces Islamic reason of UII lecturers. The theory of Islamic reason that used in this research is by integration the theory of Mark Woodward, Peter G. Riddell, and Kuntowijoyo. Having done the research process, and the classification of two typologies of UII lecturer faculty of exact and non-exact. The result of this research has revealed that Islamic reason of UII lecturers of exact faculties tend to be classisfied into Modernist Islam and lecturers of nonexact faculties can be regarded as Neomodernism Islam.